Structural Health Monitoring Using Chirp-Through Transmission and Macro Fiber Composite Transducers - Tanaka, Daniele Yoshie [UNESP]; De Almeida, Vinicius A. D.; De Sousa, Giovanni Oliveira; Brandao, Dennis; Aguiar, Paulo Roberto [UNESP]; C., Pedro Oliveira (Institute of Electrical and Electronics Engineers (IEEE), 2025)
The present work proposes the use of the macro fiber composite (MFC) transducer for damage detection through ultrasonic wave propagation. The methodology is based on the transmission and reception of ultrasonic waves accomplished through an innovative sensor monitoring approach called chirp-through transmission (CTT), in which a low-cost piezoelectric diaphragm is used as a transmitter and, as presented in this paper, the mentioned MFC transducer is used as a receiver. The acoustic waves were generated in the chirp form with a $500-\text{ms}$ time window and frequencies from 1 Hz to 250 kHz. The waves received by the MFC transducer were sampled at $2 \text{MS} / \mathrm{s}$. The damage tests were induced by mass addition, which included attaching three metallic nuts of increasing size to the aluminum beam chosen as the structure under inspection. To accurately assess damage using the received acoustic waves, preliminary tests were conducted on the structure in its healthy condition. This initial evaluation established a baseline for comparison. Subsequently, tests were performed under different conditions of damage, allowing for a comprehensive analysis and clear differentiation between conditions. A study was also conducted on the frequency content of the received waves to select the most representative frequency bands. The results demonstrated a satisfactory characterization of the actual structure condition obtained by the representative metrics root-mean-square deviation (RMSD), correlation coefficient deviation metric (CCDM), and root mean square (RMS) computed at the frequency bands of $100-125 \text{kHz}$ and $150-175 \text{kHz}$. Based on the results, the MFC transducer used in cooperation with CTT can be a simple and effective sensor monitoring tool for non-destructive applications.